Estrategia de innovación como factor determinante del éxito de las cooperativas vitivinícolas de Castilla La Mancha - Peña García-pardo, Isidro; Fernández Moreno, María Valle (REVESCO. Revista de Estudios Cooperativos, 2009)
The search for competitive advantages as one of the main activities of a company has become a principle of contemporary theories on Strategic Management (Teece, Pisano and Shuen, 1997). Innovation facilitates a company's adaptation to the global competitive environment, representing the important strategic role that it has to play in relation to managerial performance and, as such, underlines the growing importance of innovation and the use of a company's technological assets. This paper therefore studies the effect of the results of four dimensions of technological innovation strategy on a sample of wine cooperatives from Castilla-La Mancha.
Keywords: Innovation; Cooperatives; Performance